Evolution of Sustainable Finance and its Opportunities: A Bibliometric Analysis - Paul Thomas, K.; Rajini, G. (Indian Journal of Information Sources and Services, 2024)
With the worldwide promotion of sustainable development, companies across all sectors strive for high profitability while prioritizing the balance between human activities and the natural environment. Sustainable Finance (SF) is proposed in response to this context. This article retrieves 650 papers on SF and energy policies from the Web of Science and Scopus database. Initially, the research does an analytical, statistical analysis that includes several aspects, such as general growth, publishing sources, research locations, and prominent scientific research institutes. The research uses the clustering method to identify the prevailing areas of study in recent years and forecast future research directions. This research identifies significant publications, esteemed experts, discoveries, and forthcoming SF and energy policy research areas. This study enables a systematic and thorough comprehension of SF and energy policy studies. Future research opportunities lie in sustainable bonds, government aid, and greenhouse gas emissions. Future investigations can be conducted by integrating Fintech, big data, and blockchain technology.